Innovations in Marketing Strategies to Enhance the Value-Added of Forestry Products in the Perspective of Sustainable Business - Dodi Sukmayana (GoAcademica Research & Publishing, 2023)
Innovative marketing techniques are now essential for raising the value-added of products in the age of globalization and intensifying market competition, particularly in the forestry industry. This article examines numerous cutting-edge marketing techniques that can be used to raise the value-added of forestry products while taking into account sustainable business practices. This study uses a literature review methodology to look at contemporary writings on marketing tactics, the added value of forestry goods, and the idea of sustainable business. The study's findings suggest that integrating digital technology, in-depth market knowledge, and sustainable practices might lead to efficient marketing methods that enhance the value-added of forestry goods. Furthermore, including sustainable business practices into marketing plans can improve customer confidence in brands, the longevity of natural resources, and brand reputation. In order to create greater value-added and sustainable enterprises, this article offers strategic advice for forestry sector stakeholders to adapt and adopt innovation in their marketing strategies.